Analyzing HOTS Labeled Questions in An EFL Fifth Grade Elementary School Textbook - Galang Adhitia Mahardhika; Yanty Wirza; Faksi Rana Al-Kahfi; Ahmad Dindang Mababaya (IJELTAL (Indonesian Journal of English Language Teaching and Applied Linguistics), 2025)
The textbook used for fifth grade elementary students in an elementary school in Kuningan, West Java claims to offer Higher Order Thinking Skill (HOTS) questions on the cover of the textbook and some questions have been labeled as HOTS questions. This research investigated the validity of this claim, analyzing the levels of cognitive domain of each question to determine whether the labeled questions are truly HOTS questions or Lower Order Thinking Skills (LOTS) questions. This study conducted qualitative research with document analysis of HOTS labeled questions in the textbook entitled “Modul Pembelajaran Bina Prestasi Bahasa Inggris Kelas 5 Untuk SD/MI'' published by CV Larassukma which were analyzed using a revised Bloom’s taxonomy framework. Additionally, an interview with a fifth grade English teacher was conducted to explore the teacher's perspective regarding the HOTS questions in the textbook. The results revealed that most labeled HOTS questions are in fact LOTS questions (90.9%), with a majority covering Remembering (C1), followed by Understanding (C2), and Applying (C3). Only two questions were qualified as HOTS, particularly Creating (C6) questions (9.1%). The teacher's perspective mirrored these findings, indicating the inconsistency between the textbook's claims with its actual content, also discussing the textbook’s effectiveness and the teacher’s approach for implementing HOTS in the classroom. This study provides valuable insights for teachers, curriculum designers, textbook creators, and publishers, emphasizing the need for accurate representation of HOTS in educational materials to enhance the quality of future education.